2007
DOI: 10.1111/j.1754-4505.2007.tb00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary parameters in infants aged 12 to 60 months with Down syndrome

Abstract: The purpose of this study was to measure certain components in whole saliva from children with Down syndrome aged 12 months to 60 months. Twenty children with Down syndrome were compared with 18 children without Down syndrome. Whole saliva was collected under slight suction and the salivary pH was measured with a portable pH meter soon after collection. Electrolyte concentrations were determined by inductively coupled argon plasma with atomic emission spectrometry. Sialic acid was determined by thiobarbituric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 27 publications
5
26
2
7
Order By: Relevance
“…These results are not consistent with other studies, which have shown a decrease in salivary peroxidase activity in children with DS aged 6-10 and 1-5 years, respectively. 20,21 In contrast, the total protein content observed in the present study was significantly higher in patients with DS (3.65 AE 1.28 mg/dL) than in controls (2.16 AE 0.69 mg/dL). This finding agrees with the studies cited above, which showed a significant increase in salivary total protein content in children with DS aged 6-10 and 1-5 years, respectively.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…These results are not consistent with other studies, which have shown a decrease in salivary peroxidase activity in children with DS aged 6-10 and 1-5 years, respectively. 20,21 In contrast, the total protein content observed in the present study was significantly higher in patients with DS (3.65 AE 1.28 mg/dL) than in controls (2.16 AE 0.69 mg/dL). This finding agrees with the studies cited above, which showed a significant increase in salivary total protein content in children with DS aged 6-10 and 1-5 years, respectively.…”
Section: Discussioncontrasting
confidence: 74%
“…This finding agrees with the studies cited above, which showed a significant increase in salivary total protein content in children with DS aged 6-10 and 1-5 years, respectively. 20,21 Further research in this area is necessary since the results from studies investigating salivary peroxidase activity are conflicting.…”
Section: Discussionmentioning
confidence: 98%
“…Salivary flow. With regard to salivary factors, no significant differences were observed in the concentrations of sialic acid, calcium, phosphorus, and magnesium between 20 Down syndrome and 18 control children aged 1-5 years old [49]. In contrast, protein and sodium concentrations were higher in the Down syndrome group, whereas flow rate, pH level, amylase and peroxidase activities, and potassium concentration were lower.…”
Section: Salivary Factorscontrasting
confidence: 47%
“…A time course experiment in yeast medium, supplemented with 0.2% wt/vol sialic acid, showed that the effect of sialic acid on the attachment of pneumococci to surfaces occurred after a few hours of incubation, corresponding to the exponential phase of growth (figure 3C). The sialic acid concentration found to be sufficient to induce biofilm formation was between 1 and 3 g/mL (figure 3D), a concentration comparable to that of free sialic acid in human saliva [23][24][25]. Pneumococci carry 2-3 genes that code for sialidases/neuraminidase [26,27].…”
Section: Pneumococcal Biofilm Formation Is Induced By Sialic Acidmentioning
confidence: 98%